2005
DOI: 10.1007/s10286-005-0281-8
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic skin response in premenstrual syndrome

Abstract: Premenstrual syndrome is a term which includes a broad group of emotional, behavioral and physical symptoms that occur for several days before menses and subside following the menstrual period. Many women experience premenstrual syndrome symptoms, particularly physical ones such as breast tenderness and swelling. Approximately 5-10% women suffer from severe premenstrual syndrome and another 30-40% have moderate symptoms. Premenstrual syndrome continues to be an unsolved problem. In this study, we evaluated 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The absence of any influence of the phase of the cycle on the reflex vascular responses, although unexpected in terms of the hormonal changes, is broadly in agreement with the findings of others, who observed no effect of phase of the menstrual cycle on the responses to lower body suction [21,28,38], to quiet standing [24] or to other physiological stimuli [2,5,34]. However, it is suggested that there are alterations in orthostatic tolerance associated with the menstrual cycle when additional vasodilator stress is applied, such as whole body heating [28].…”
Section: Discussionsupporting
confidence: 91%
“…The absence of any influence of the phase of the cycle on the reflex vascular responses, although unexpected in terms of the hormonal changes, is broadly in agreement with the findings of others, who observed no effect of phase of the menstrual cycle on the responses to lower body suction [21,28,38], to quiet standing [24] or to other physiological stimuli [2,5,34]. However, it is suggested that there are alterations in orthostatic tolerance associated with the menstrual cycle when additional vasodilator stress is applied, such as whole body heating [28].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are consistent with results obtained by Ozisik HI (2005) who concluded that the sympathetic skin response was similar during the late luteal and follicular phases of both PMS subjects and non PMS subjects. (18) This study identified irritability as the most common symptom where 94% of the PMS subjects suffered from irritability.…”
supporting
confidence: 93%
“…(18) This study identified irritability as the most common symptom where 94% of the PMS subjects suffered from irritability. The next common symptoms were depression and emotional liability with 79% of the PMS subjects.…”
mentioning
confidence: 92%
“…Ozisik et al, observed no statistical difference in the sympathetic response during the luteal phase between the PMS patients and the control group. 20 Assoc and Magos investigated that the patient's premenstrual distress appeared to arise mainly from chronically high autonomic activity. 4 Koeske found a premenstrual increase in skin conductance, a test to measure the sympathetic axis.…”
Section: Discussionmentioning
confidence: 99%